THE EFFECTIVENESS OF COACHING USING SBAR (SITUATION, BACKGROUND, ASSESSMENT, RECOMMENDATION) COMMUNICATION TOOL ON NURSING SHIFT HANDOVERS - Vitri Dyah Herawati; Devi Nurmalia; Tri Hartiti; Luky Dwiantoro (Belitung Raya Foundation, Indonesia, 2018)
Background: The SBAR (situation, background, assessment, recommendation) method assists nurses in communicating information in nursing shift handover. Inaccurate shift handover can have a serious impact on patients due to poor communication. Optimal resource development can be done by coaching as the best guidance method from manager for directional discussion and guidance activity to learn to solve problem or do better job and build nursing leadership culture in clinical service. Objective: To analyze the effectiveness of coaching method using SBAR communication tool on nursing shift handovers. Methods: This was a quasi-experimental study with pretest posttest control group design. Fifty-four nurses were selected using a consecutive sampling, which 27 assigned in the experiment and control group. An observation checklist was developed by the researchers based on the Theory of Lardner to evaluate the effectiveness of the implementation of coaching using SBAR on nursing shift handover. Independent t-test, Mann-Whitney test and Wilcoxon test were used for data analyses. Results: There was an increase in coaching ability of head nurses in the implementation of SBAR in nursing handover after 2-weeks and 4-weeks of coaching. There was also a significant improvement of the use of SBAR on nursing shift handover in the experiment group (p <0.05) compared to the control group. Conclusion: Coaching using SBAR (situation, background, assessment, recommendation) communication tool was effective on nursing shift handovers. There was a significant increase of the capability of head nurses and nursing shift handovers after given coaching intervention.